Clinical outcomes for patients with liver-limited metastatic colorectal cancer: Arguing the case for specialist hepatobiliary multidisciplinary assessment. Issue 9 (September 2016) - Thillai, K.; Repana, D.; Korantzis, I.; Kane, P.; Prachalias, A.; Ross, P.
Abstract: In patients with liver-limited metastatic colorectal cancer, hepatic resection can offer a significant survival benefit over systemic therapy alone. Specialist hepatobiliary multidisciplinary meetings are currently believed to provide the best forum to discuss the management for these patients. A retrospective analysis was undertaken of patients diagnosed with liver-limited metastatic colorectal cancer over 6 months within a cancer network in the United Kingdom. In addition, patients who were diagnosed but not referred to the hepatobiliary meeting were discussed within a virtual multi-disciplinary setting. Contributors were blinded and proposed management recorded. 159 newly diagnosed patients with liver-limited metastatic colorectal cancer were identified. 68 (43%) were referred at initial diagnosis and 38 (24%) referred following systemic treatment. 35 (51%) who were discussed at baseline underwent a subsequent hepatectomy or radiofrequency ablation, as did 18 (47%) patients referred after chemotherapy. Of the remaining 53 (33%) patients not referred, imaging was available for 31 (58%). Decisions regarding potential liver-directed therapy were discussed within a multi-disciplinary setting. 13 (42%) were identified as resectable or potentially resectable and 11 (36%) may have been suitable for a clinical trial. In reality, none of these 31 patients (100%) underwent surgery or ablation. Whilst the majority of patients with liver-limited metastatic colorectal cancer were referred appropriately, this study demonstrates that a significant number with potentially resectable disease are not being discussed at specialist meetings. A review of all diagnosed cases would ensure that an increased number of patients are offered hepatic resection or ablation.